The Influence of Parental Leadership Type on Socialization Process in Namorambe Junior High School Students - Methodius Tigor (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
Abstrak. Human beings as social beings will not be separated from the association with people around him. This is a very important need for humans. In the association there is a process of socialization, in everyday life the process of socialization of a person is not always good but there is the opposite. What is revealed in this study is how much influence of the type of parental leadership on the socialization process of the students of SMP Negeri 1 Namorambe. The research sample studied was 40 students of grade VIII Smp Negeri 1 Namorambe. The method used is descriptive method. To obtain the data, researchers used a closed questionnaire. The data obtained in the processing is adjusted to the criteria of items number 1 to 22, namely: 1.00 – 1.66 belongs to the category of authoritarian leadership type, 1.67 – 2.33 is laizer faire leadership type, 2.34 – 3.00 including democratic type. For items 23 to 45 use kriteri 1.00 – 1.75 less once, 1.76 – 2.50 less, 2.51 – 3.25 good, and 3.26 – 4.00 including an excellent socialization process. The hypotheses that are enforced are there is a significant influence between the type of parental leadership in the family to the socialization process of the child (student). From the calculations, the type of leadership of the parents of the students is mostly Laizer Faire. While the correlation between the two variables is positive where rcalculates the > rtable is r(h) 0.99 > r(t) 0.312. Therefore, the accepted hypothesis is that there is an influence of the type of parental leadership in the family on the socialization process of students. To see the amount of influence exerted from the calculation results obtained 98 %. Thus, there is a positive and meaningful influence between parental leadership on the socialization process in students of SMP Negeri 1 Namorambe